Does COVID-19 impact female and male farmers differentially? An insight from a study in Eastern Gangetic Plains of India - Das, Soumyadeep; Das, Kalyan Kanti; Ghosh, Arunava; Lepcha, Achyoung; Kumar Chowdhury, Apurba; Rola-Rubzen, Maria Fay (Uttar Banga Krishi Viswavidyalaya, 2023)
This article aims to throw some light on the differential impact of COVID-19 and consequent coping strategies of women and men farmers, using household survey data from the functional heads of 602 farming households of two northern districts of West Bengal, India. Studies showed that lockdowns induced by COVID-19 had far-reaching impacts on the rural agricultural sector, especially on women farmers. The pandemic had negative consequences on local food systems and supply networks. Now, the question is: How did it affect the farming folk regarding concerns, constraints, coping strategies, etc.? Our analysis found no significant difference between the female and male farmers regarding concerns and constraints faced, and the coping strategies adopted. About 70% of the respondents perceived market access limitation to be the topmost concern and about 71% of the respondents relied on their own savings as the topmost coping strategy. The study indicates an almost equal participating attitude of farm women along with the male in perceiving the concerns, working out the response strategies and others during this pandemic. We need proper planning and initiatives to foster this silent and positive change in the economy.